The Effect of Papinka Learning Media in Improving Cognitive Skills of Children 5-6 Years of Age - Anjelita, Anggi; Syur'aini, Syur'aini (Universitas Negeri Padang, 2024)
This research was motivated by the low cognitive abilities of children aged 5-6 years at KB Jannatul Na'iem Kampung Padang Pariaman. Children's low cognitive abilities are caused by several factors, namely lack of facilities, biological maturity, physical activity, environmental interactions, balance of new information. Of these many factors, less attractive learning facilities/media is the main factor. This research aims to determine the increase in cognitive abilities of children aged 5-6 years using papinka media at KB Jannatul Na'iem. This type of research is quantitative with a quasi-experimental method. The research design used was pretest and posttest. The population of this study was 21 children. The research sample consisted of 21 children taken from the entire population. Purposive sampling technique. Data analysis used the T test. The results of the research can be concluded (1) before taking action (pretest), children's cognitive abilities were grouped into early development stages, (2) after taking action (posttest), children's cognitive abilities were grouped into developing stages according to expectations . and (3) there is a significant influence of papinka media in improving the cognitive abilities of children aged 5-6 years. Keywords: Papinka Media, Children's Cognitive Abilities.